Validasi Potensi Tsunami Berdasarkan Estimasi Durasi Patahan dan Pemodelan Tsunami di Wilayah Barat Sumatra (Studi Kasus: Gempa Bumi Nias 2005 dan Mentawai 2010) - Sayyidatul Khoiridah; Moh Ikhyaul Ibad; Wiko Setyonegoro, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Validation of Potential Tsunami Based on Rupture Duration Estimation and Tsunami Modeling in the West Sumatran Region (Case Study: Nias 2005 and Mentawai 2010 Earthquakes). This research was conducted in the earthquake areas in the West Sumatra to determine the characteristics of tsunami generation through estimation of rupture duration and modeling of tsunamis. The case studies were carried out at two incidents: earthquake in Nias on March 28, 2005 and in Mentawai on October 25, 2010. The purpose of this study was to estimate the characteristics of potential earthquaketriggering tsunamis in the western region of Sumatra based on the duration of rupture, which was then validated by a tsunami modeling. A method for validation was carried out by analyzing a potency of a tsunami based on the earthquake source (source modeling), the propagation of the tsunami wave (ocean modeling), and the height of the tsunami (run-up tsunami). The results showed the duration of the earthquakes in Nias rupture (2005) and Mentawai rupture (2010) were more than 50 seconds, thus, both earthquakes promoted tsunami. The results of tsunami propagation revealed that the tsunami had spread to some areas near the source of the Nias earthquake after 58 minutes and 20 seconds. The area affected by the Nias tsunami included the Salaut island, a section at northwestern Simeulue, a section at southwestern Simeulue, Babi island, Bangkuru island, Tuangku island, Singkil, Sarangbaung, Asu island, southwestern Lagundri Nias, and Northwestern Batu island. The highest tsunami hit Babi island with the magnitude of 13.80 m. Moreover, the tsunami affected the wider areas in Mentawai including the beaches of Batimonga, Ghobi, Tumale, Pasangan, Sabeugunggung, Malacopa, and Asahan with the highest value of run-up on Malacopa beach was 8.17 m.